ASSESSMENT OF DIABETES KNOWLEDGE AMONG PATIENTS ATTENDING A DIABETIC CLINIC AT A TERTIARY CARE PUBLIC HOSPITAL IN BAHAWALPUR (The Research of Medical Science Review, 2025)
Background: The prevalence of diabetes mellitus, a chronic metabolic disease, is rising worldwide. Sufficient patient awareness is necessary for both effective care and the avoidance of problems. Improving health outcomes requires evaluating diabetic patients' understanding of diabetes. Aims and Objectives: The purpose of this study is to assess patients' knowledge about diabetes at a diabetic clinic at a public tertiary care hospital in Bahawalpur. Finding knowledge gaps in diabetes, its management, risk factors, complications, and preventive strategies is the goal. Methodology: A descriptive-analytical, quantitative study was conducted from November 2023 to March 2024. A total of 271 diabetic patients meeting the inclusion criteria were selected through convenient sampling technique. A standardized, self- administered questionnaire encompassing demographic information, clinical history, and diabetes-related knowledge was used to gather data. Data analysis was done using descriptive statistics. Results: Of the participants, 91% were between the ages of 30 and 50, and 72.6% were men. The most common kind of diabetes was type 2 (94%). Just 52% of respondents properly defined diabetes as having high blood sugar, and 51% were unaware that diabetic health education was available. Just 26.2% of respondents understood that diabetes is inherited, indicating a lack of knowledge of risk factors and complications. Just 21.4% of respondents reported making dietary changes, compared to 48.7% who reported routine blood sugar monitoring. Conclusion: According to the report, patients' understanding of diabetes is seriously lacking. To improve self-care behaviors and avoid complications, better patient education programs that emphasize diabetes management, risk factors, and lifestyle changes are crucial.